How repeatable is microevolution on islands? Patterns of dispersal and colonization-related plant traits in a phylogeographical context - García-Verdugo, Carlos; Caujapé-Castells, Juli; Mairal, Mario; Monroy, Pedro (Annals of botany, 2019)
BACKGROUND AND AIMS: Archipelagos provide a valuable framework for investigating phenotypic evolution under different levels of geographical isolation. Here, we analysed two co-distributed, widespread plant lineages to examine if incipient island differentiation follows parallel patterns of variation in traits related to dispersal and colonization. METHODS: Twenty-one populations of two anemochorous Canarian endemics, Kleinia neriifolia and Periploca laevigata, were sampled to represent mainland congeners and two contrasting exposures across all the main islands. Leaf size, seed size and dispersability (estimated as diaspore terminal velocity) were characterized in each population. For comparison, dispersability was also measured in four additional anemochorous island species. Plastid DNA data were used to infer genetic structure and to reconstruct the phylogeographical pattern of our focal species. KEY RESULTS: In both lineages, mainland-island phenotypic divergence probably started within a similar time frame (i.e. Plio-Pleistocene). Island colonization implied parallel increases in leaf size and dispersability, but seed size showed opposite patterns of variation between Kleinia and Periploca species pairs. Furthermore, dispersability in our focal species was low when compared with other island plants, mostly due to large diaspore sizes. At the archipelago scale, island exposure explained a significant variation in leaf size across islands, but not in dispersability or seed size. Combined analyses of genetic and phenotypic data revealed two consistent patterns: (1) extensive within-island but very limited among-island dispersal, and (2) recurrent phenotypic differentiation between older (central) and younger (peripheral) island populations. CONCLUSIONS: Leaf size follows a more predictable pattern than dispersability, which is affected by stochastic shifts in seed size. Increased dispersability is associated with high population connectivity at the island scale, but does not preclude allopatric divergence among islands. In sum, phenotypic convergent patterns between species suggest a major role of selection, but deviating traits also indicate the potential contribution of random processes, particularly on peripheral islands.
Keywords: Španělsko; Life History Traits; biologická evoluce; Phylogeography; Spain; Periploca; Plant Dispersal; Allopatric differentiation; seed size; Kleinia neriifolia; island phylogeography; Asteraceae; ostrovy; leaf size; Periploca laevigata; Islands; fylogeografie; zvláštnosti životní historie; distribuce rostlin; Biological Evolution; Canary Islands; genetic drift; wind-dispersal traits